Effectiveness of precooling the injection site using tetrafluorethane on pain perception in children - Nithasha N Hameed; Sharan S Sargod; Sham S Bhat; Sundeep K Hegde; Muhsin Mohammed Bava (Wolters Kluwer Medknow Publications, 2018)
Background: Injection of local anesthesia is one of the most important reasons for avoidance behavior in children. Applying a topical anesthetic before injection is the most popular way to control pain; however, topical anesthetics have some shortcomings such as longer duration of action, displeasing taste, and spread of the anesthetic agent to noninjection site areas. Cryoanesthesia using refrigerant as a topical anesthesia is being studied as an alternative to overcome the shortcomings of topical anesthetics and has shown promising results. Materials and Methods: In this split-mouth design study, 50 children of aged 8-10 years who required bilateral mandibular local anesthesia administration were selected. In the first visit, application of topical anesthetic spray (lidocaine) on one side and during the second appointment cryoanesthetic tetrafluorethane on the other side was used before local anesthetic administration. Patients were asked to report their discomfort and pain using visual analog scale (VAS) (subjective method). Patients' pain perception during injection is assessed by sound, eye, and motor (SEM) scale by the dentist (objective method). Results: The results were statistically analyzed using paired Wilcoxon signed-rank test and Mann-Whitney tests. In VAS scale (subjective method), pain scores were significantly lower in tetrafluorethane group when compared with lidocaine group. In SEM scale (objective method), pain scores were lower in tetrafluorethane group when compared with lidocaine group, but it was statistically insignificant. Conclusion: Precooling the injection site using refrigerant tetrafluorethane spray has shown to be effective in eliminating pain before local anesthesia administration in children when compared with topical anesthetic lidocaine spray.